Colloidal Magnetic Heterostructured Nanocrystals with Asymmetric Topologies: Seeded-Growth Synthetic Routes and Formation Mechanisms - Scarfiello, Riccardo; Nobile, Concetta; Cozzoli, P. Davide (Frontiers in Materials, 2016)
Colloidal inorganic nanocrystals, free-standing crystalline nanostructures generated and processed in solution phase, represent an important class of advanced nanoscale materials owing to the flexibility with which their physical–chemical properties can be controlled through synthetic tailoring of their compositional, structural and geometric features and the versatility with which they can be integrated in technological fields as diverse as optoelectronics, energy storage/ conversion/production, catalysis and biomedicine. In recent years, building upon mechanistic knowledge acquired on the thermodynamic and kinetic processes that underlie nanocrystal evolution in liquid media, synthetic nanochemistry research has made impressive advances, opening new possibilities for the design, creation and mastering of increasingly complex “colloidal molecules”, in which nanocrystal modules of different materials are clustered together via solid-state bonding interfaces into free-standing, easily processable multifunctional nanocomposite systems. This Review will provide a glimpse into this fast-growing research field by illustrating progress achieved in the wet-chemical development of last-generation breeds of all-inorganic heterostructured nanocrystals (HNCs) in asymmetric non-onionlike geometries, inorganic analogues of polyfunctional organic molecules, in which distinct nanoscale crystalline modules are interconnected in hetero-dimer, hetero-oligomer and anisotropic multidomain architectures via epitaxial heterointerfaces of limited extension. The focus will be on modular HNCs entailing at least one magnetic material component combined with semiconductors and/or metals, which hold potential for generating enhanced or unconventional magnetic properties, while offering diversified or even new chemical-physical properties and functional capabilities. The available toolkit of synthetic strategies, all based on the manipulation of seeded-growth techniques, will be described, revisited and critically interpreted within the framework of the currently understood mechanisms of colloidal heteroepitaxy.